2009
DOI: 10.1063/1.3248478
|View full text |Cite|
|
Sign up to set email alerts
|

Teaching and learning astronomy in the 21st century

Abstract: A national study of teaching and learning in courses that introduce astronomy to nonscience majors shows that interactive learning strategies can significantly improve student understanding of core concepts in astrophysics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 13 publications
3
30
0
Order By: Relevance
“…Hence, we used class-average normalized gain (g) as a measure of effectiveness for our educational intervention, in addition to learning gain. Hake categorized a class-average normalized gain of 0.1–0.29 as low gain (g), 0.3–0.69 as medium gain and 0.7–1.0 as high gain [15, 18]. In our study, we observed the class-average normalized gain (g) of 0.4872 (48.72 %) in the intervention group as compared with 0.2656 (26.56 %) in control group.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we used class-average normalized gain (g) as a measure of effectiveness for our educational intervention, in addition to learning gain. Hake categorized a class-average normalized gain of 0.1–0.29 as low gain (g), 0.3–0.69 as medium gain and 0.7–1.0 as high gain [15, 18]. In our study, we observed the class-average normalized gain (g) of 0.4872 (48.72 %) in the intervention group as compared with 0.2656 (26.56 %) in control group.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties understanding topics in basic astronomy are well documented [25][26][27][28]. However, previous research has focused on conceptual ideas, such as causes for the seasons, the phases of the moon, and night and day.…”
Section: Instruction: Immersion Programmentioning
confidence: 99%
“…This change was initiated by physics education research that showed active engagement of students produced significantly greater learning gains than passive lecture (Hake 1998). This new approach to teaching has now spread to other sciences, including astronomy (Prather et al 2009). The introductory astronomy course is one of the most popular science courses for non-science majors at the college level.…”
Section: Introductionmentioning
confidence: 98%